Religious Guidance in Students - Sholahuddin, Sholahuddin; Nasution, Fauziah; Muhlison, Muhlison (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2025)
Religious coaching in schools has an important role in shaping the character and personality of students to be in accordance with Islamic teachings. In adolescence, students are in a phase of self-discovery that is vulnerable to negative influences, so appropriate religious guidance is needed through systematic and continuous activities. This study aims to describe the implementation of religious coaching at SMA Negeri 1 Kotapinang and identify the inhibiting and supporting factors in the process. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that religious guidance is carried out through several programs, namely Islamic Spiritual activities (ROHIS), congregational Dzuhur prayers, and tajweed learning. These activities are able to foster students' spiritual awareness and strengthen religious values in daily life. However, there are several obstacles such as low student interest, the influence of a less conducive environment, and limited facilities. On the other hand, the success of this coaching is supported by cooperation between teachers, the involvement of school principals, and a strict supervision system. Therefore, religious guidance needs to be strengthened in order to be able to produce a young generation with noble character and Islamic character.